2006
DOI: 10.2109/jcersj.114.911
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Zinc Oxide and Layered Basic Zinc Salts from Aqueous Solutions Containing Amino Acids and Dipeptides

Abstract: Deposition experiments from aqueous solutions of zinc nitrate were performed in a bio-inspired way using biomolecules as directing agents. A global overview of the effect of various amino acids 8 and dipeptides 21 was done in term of structure and morphology of the obtained coating. The selection of certain biomolecules leads to the formation of smooth ZnO thin films. Variations of the amino acid chemical function and the sequence used within the peptides combination give rise to a wide variety of morphologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…The most commonly used approach is that involving SDAs ranging from simple molecules, such as amines [13][14][15][16] and anionic species, [17][18][19][20][21] to polymers (DBCP, [22][23][24][25][26][27][28][29] PVP, [30][31][32][33][34][35][36][37][38][39][40][41][42] PAM, 29 and PAH 43 ) and biomolecules. [44][45][46][47][48][49][50][51][52] The SDAs have been shown to affect the morphology of ZnO by imposition of effects on nucleation and/or growth of the crystals. Among these SDAs, biomolecules have received little attention in ZnO synthesis because of their complexity, high cost, and sensitivity to reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most commonly used approach is that involving SDAs ranging from simple molecules, such as amines [13][14][15][16] and anionic species, [17][18][19][20][21] to polymers (DBCP, [22][23][24][25][26][27][28][29] PVP, [30][31][32][33][34][35][36][37][38][39][40][41][42] PAM, 29 and PAH 43 ) and biomolecules. [44][45][46][47][48][49][50][51][52] The SDAs have been shown to affect the morphology of ZnO by imposition of effects on nucleation and/or growth of the crystals. Among these SDAs, biomolecules have received little attention in ZnO synthesis because of their complexity, high cost, and sensitivity to reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Secondly, some biomoleculedirected syntheses have been shown to impose exquisite control on ZnO morphology/structure; [44][45][46]48,50,51,55 improve ZnO crystallinity; 50 template ZnO formation; 47,49,52,56 catalyze ZnO formation; 57,58 and also suppress ZnO formation. 44,45 These diverse effects can possibly be used to tune the morphology/ structure-related properties of ZnO and thus its applications. Thirdly, biomolecules show remarkable recognition capabilities, functional specificity and multi-functional characteristics which may contribute to high efficiency and accuracy in ZnO structure tailoring.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These NPs grow in solution under the presence of histidine. Gerstel et al [26,27] found that histidine controls NP growth and is incorporated in the resulting films. XRD measurements show that the deposited ZnO is X-rayamorphous (data not shown).…”
Section: Resultsmentioning
confidence: 99%